2013
DOI: 10.3109/09593985.2012.761308
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Persian version of Functional Index Questionnaire (FIQ) and Modified FIQ in patients with patellofemoral pain syndrome

Abstract: The aim of this investigation was to culturally translate and validate the Functional Index Questionnaire (FIQ) and Modified FIQ (MFIQ) in patients with patellofemoral pain syndrome (PFPS). A sample of 100 patients with PFPS completed the FIQ and MFIQ, and Short-Form 36 (SF-36) Health Survey in the first session. The FIQ and MFIQ were re-administered to a sample of 47 patients to evaluate test-retest reliability. Test-retest reliability and internal consistency were evaluated by the intraclass correlation coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The SF-36 sub-scales of ‘social function’ and ‘mental health’ both demonstrated small correlations with the Functional Index questionnaire, r=0.23 and r=0.15, respectively (Q3) 34. All SF-36 subscales apart from role emotional (r=0.08) demonstrated small correlations with the Modified Functional Index Questionnaire (Q3) 34…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SF-36 sub-scales of ‘social function’ and ‘mental health’ both demonstrated small correlations with the Functional Index questionnaire, r=0.23 and r=0.15, respectively (Q3) 34. All SF-36 subscales apart from role emotional (r=0.08) demonstrated small correlations with the Modified Functional Index Questionnaire (Q3) 34…”
Section: Resultsmentioning
confidence: 99%
“…Supporting comparative data were three high-rating single-group studies (Q337 38;Q445),demonstrating elevated psychological factors compared with six single-group studies that found no difference in measures. Of the latter, four rated poorly (Q126 28 42;Q235) and two rated highly Q334;Q441). Thus, many of these findings suggest that coping strategies including catastrophising may differ in those with PFP, though the clinical relevance of the size of this difference is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Other inclusion criteria were a positive Zohler (Appendix 1) or Clarke sign (Appendix 2), patellar tenderness, and an average pain level in the preceding month of at least 3 on a visual analog scale (VAS) . Additional inclusion criteria were insidious onset of symptoms (nontraumatic), a score of at least 11 on the Persian version of the Functional Index Questionnaire (FIQ), age ≤ 40 years (to reduce the likelihood of osteoarthritic changes), unilateral PFPS, body mass index between 18.5 and 24.9 kg/m 2 , normal menstrual cycle, that is, a self‐reported cycle duration of 22‐36 days with no more than 3 days of variation in cycle length during the previous 3 months, and not using oral contraceptive hormones for 3 months before the start of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The two further studies highlighted by Professor Selfe (Nijs et al 2006;Negahban et al 2013) were also excluded from our review. The abstract for Nijs et al (2006) focused on the diagnostic validity of five clinical PFPS tests without reference to their examination of the measurement properties of a Dutch version of the MFIQ (MFIQ-DV), and this article was therefore excluded at the title/abstract screening phase.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The abstract for Nijs et al (2006) focused on the diagnostic validity of five clinical PFPS tests without reference to their examination of the measurement properties of a Dutch version of the MFIQ (MFIQ-DV), and this article was therefore excluded at the title/abstract screening phase. The Negahban et al (2013) paper was not eligible for inclusion as it was published after our search to August 2013.…”
Section: Accepted Manuscriptmentioning
confidence: 99%